2022
DOI: 10.1186/s12889-022-12702-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of overweight, obesity and central obesity and factors associated with BMI in indigenous yaqui people: a probabilistic cross-sectional survey

Abstract: Background The Yaquis are an Indigenous group who inhabit in the state of Sonora in northwestern Mexico. This group has experienced changes in their lifestyle, moving from a traditional lifestyle to a more modern one, resulting in an increase of obesity and its comorbidities. However, few studies have been done in this group. The aim of this study was to determine the prevalence of overweight, obesity and central obesity and to identify the factors associated with body mass index (BMI) in a rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 40 publications
0
3
0
1
Order By: Relevance
“…11 Asimismo, en la etnia yaqui se ha evidenciado el proceso de adquisición y asimilación de características de otra cultura (aculturación), 12 con las consecuentes modificaciones en su estilo de vida, cambios en su alimentación al adoptar un estilo de vida occidental, con el paso de una ingesta basada en legumbres y cereales al consumo elevado de alimentos procesados densos en energía. 13,14 Estos cambios han provocado alteraciones en el estado nutricional de la población, la cual ha desarrollado obesidad y, posteriormente, problemas de salud como enfermedades crónicas no transmisibles. 15 Un estudio probabilístico realizado recientemente en adultos de este grupo ha revelado graves problemas de salud: 71.5 % tiene sobrepeso/obesidad, 21.3 % padece hipertensión arterial 13 y 10.5 % cuenta con diagnóstico previo de diabetes.…”
Section: Antecedentesunclassified
“…11 Asimismo, en la etnia yaqui se ha evidenciado el proceso de adquisición y asimilación de características de otra cultura (aculturación), 12 con las consecuentes modificaciones en su estilo de vida, cambios en su alimentación al adoptar un estilo de vida occidental, con el paso de una ingesta basada en legumbres y cereales al consumo elevado de alimentos procesados densos en energía. 13,14 Estos cambios han provocado alteraciones en el estado nutricional de la población, la cual ha desarrollado obesidad y, posteriormente, problemas de salud como enfermedades crónicas no transmisibles. 15 Un estudio probabilístico realizado recientemente en adultos de este grupo ha revelado graves problemas de salud: 71.5 % tiene sobrepeso/obesidad, 21.3 % padece hipertensión arterial 13 y 10.5 % cuenta con diagnóstico previo de diabetes.…”
Section: Antecedentesunclassified
“…11 Moreover, in the Yaqui ethnic group, the process of acquiring and assimilating characteristics of another culture (acculturation) has been demonstrated, 12 with consequent modifications of their lifestyle, changes in their diet when adopting a Western lifestyle, with a shift from an intake based on legumes and grain products to a high consumption of energy-dense processed foods. 13,14 These changes have caused alterations in the population nutritional status, who have developed obesity and, subsequently, health problems such as chronic non-communicable diseases. 15 A probabilistic study carried out recently in adults from this group has revealed serious health problems: 71.5% were found to have overweight/obesity; 21.3%, to suffer from high blood pressure; 13 and 10.5%, to have a previous diagnosis of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 These changes have caused alterations in the population nutritional status, who have developed obesity and, subsequently, health problems such as chronic non-communicable diseases. 15 A probabilistic study carried out recently in adults from this group has revealed serious health problems: 71.5% were found to have overweight/obesity; 21.3%, to suffer from high blood pressure; 13 and 10.5%, to have a previous diagnosis of diabetes. 16 As for physical activity, productive activities with higher physical demand have been replaced by others of lower intensity, and the practice of sedentary activities has increased.…”
Section: Introductionmentioning
confidence: 99%
“…Centrándonos en Sonora, México, la prevalencia combinada de sobrepeso y obesidad en adultos indígenas Yaquis fue del 71.5%, con un 35% de la población clasificada como obesa (Serna-Gutiérrez et al, 2022). Estos datos subrayan la necesidad urgente de abordar la obesidad no solo como un desafío de salud pública, sino también como una crisis social y económica que requiere una respuesta integral y multisectorial.…”
Section: Introductionunclassified